Influence of habitual high dietary fat intake on endothelium-dependent vasodilation - Dow, Caitlin A. (Appl Physiol Nutr Metab, 2015)
High-fat diets are associated with an increased risk of cardiovascular disease. A potential underlying mechanism for the increased cardiovascular risk is endothelial dysfunction. Nitric oxide (NO)-mediated endothelium-dependent vasodilation is critical in the regulation of vascular tone and overall vascular health. The aim of this study was to determine the influence of dietary fat intake on endothelium-dependent vasodilation. Forty-four middle-aged and older sedentary, healthy adults were studied: 24 consumed a lower fat diet (LFD; 29% ± 1% calories from fat) and 20 consumed a high-fat diet (HFD; 41% ± 1% calories from fat). Four-day diet records were used to assess fat intake, and classifications were based on American Heart Association guidelines (<35% of total calories from fat). Forearm blood flow (FBF) responses to acetylcholine, in the absence and presence of the endothelial NO synthase inhibitor N(G)-monomethyl-l-arginine (L-NMMA), as well as responses to sodium nitroprusside were determined by plethysmography. The FBF response to acetylcholine was lower (~15%; P < 0.05) in the HFD group (4.5 ± 0.2 to 12.1 ± 0.8 mL/100 mL tissue/min) than in the LFD group (4.6 ± 0.2 to 14.4 ± 0.6 mL/100 mL tissue/min). L-NMMA significantly reduced the FBF response to acetylcholine in the LFD group (~25%) but not in the HFD group. There were no differences between groups in the vasodilator response to sodium nitroprusside. These data indicate that a high-fat diet is associated with endothelium-dependent vasodilator dysfunction due, in part, to diminished NO bioavailability. Impaired NO-mediated endothelium-dependent vasodilation may contribute to the increased cardiovascular risk with high dietary fat intake.